Surface sensing behavior and band edge properties of AgAlS2: Experimental observations in optical, chemical, and thermoreflectance spectroscopy - Ching-Hwa Ho; Chia-Chi Pan (AIP Advances, 2012)
Optical examination of a chaocogenide compound AgAlS2 which can spontaneously transfer to a AgAlO2 oxide has been investigated by thermoreflectance (TR) spectroscopy herein. The single crystals of AgAlS2 were grown by chemical vapor transport (CVT) method using ICl3 as a transport agent sealed in evacuated quartz tubes. The as-grown AgAlS2 crystals essentially possess a transparent and white color in vacuum. The crystal surface of AgAlS2 becomes darkened and brownish when putting AgAlS2 into atmosphere for reacting with water vapor or hydrogen gas. Undergoing the chemical reaction process, oxygen deficient AgAlO2-2x with brownish and reddish-like color on surface of AgAlS2 forms. The transition energy of deficient AgAlO2-2x was evaluated by TR experiment. The value was determined to be ∼2.452 eV at 300 K. If the sample is kept dry and moved away from moisture, AgAlS2 crystal can stop forming more deficient AgAlO2-2x surface oxides. The experimental TR spectra for the surface-reacted sample show clearly two transition features at EW=2.452 eV for deficient AgAlO2-2x and EU=3.186 eV for AgAlS2, respectively. The EU transition belongs to direct band-edge exciton of AgAlS2. Alternatively, for surface-oxidation process of AgAlS2 lasting for a long time, a AgAlO2 crystal with yellowish color will eventually form. The TR measurements show mainly a ground-state band edge exciton of E OX 1 detected for AgAlO2. The energy was determined to be E OX 1=2.792 eV at 300 K. The valence-band electronic structure of AgAlS2 has been detailed characterized using polarized-thermoreflectance (PTR) measurements in the temperature range between 30 and 340 K. Physical chemistry behaviors of AgAlS2 and AgAlO2 have been comprehensively studied via detailed analyses of PTR and TR spectra. Based on the experimental analyses, optical and chemical behaviors of the AgAlS2 crystals under atmosphere are realized. A possible optical-detecting scheme for using AgAlS2 as a humidity sensor has also been proposed.